Role of Vrishyashatavarighrit on Sukrakshaya (Oligospermia) by Studying Siddhant - Snehal V. Kukade1, Bhokardankar Prashant S 2, Milind Rampurkar3, Abhishek Joshi4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Ayurveda is oldest tradition addressing major healthcare issues in sophispticated way. There are number ofmodern medicines giving relief to the patients but having adverse effects at highest level. Ayurveda smartlynot only addresses the issues but having less side effects. Current study focuses the use of Shatavarighritinshukrakshay (oligospermia) patients. The study comes to a conclusion with a promising results in the patientsof oligospermia. The study result to reduce the burden for patients and giving light who having infertility.